Behaviour study on retirement financial planning of employees in private sector - MS. B. NEERAJA,; MR. MANOJEE. P, (The journal of contemporary issues in business and government, 2020)
The purpose of this study is to determine the factors influencing retirement planning among young professionals in the private sector .There are certain factors which determine retirement based on financial literacy, job satisfaction and savings behavior. Financial plan helps with funds. Financial plan should be goal oriented and it should take care of needs in the most crucial period of life. This paper aims to evaluate the relevance of demographic and psychological factors in making saving and investment decisions with focus on retirement financial planning. The study is based on primary as well as on the secondary data. To understand various frameworks and predict the variables, research papers and articles would be referred. Most of the people preferred bank deposits by investing for purchasing home and long-term growth but, most of the investors were not aware of investing their money in mutual funds and shares. This research would be relevant in getting insight into factors and issues faced by the individual while making financial plans for retirement. Primary data on demographic and psychological variables would be collected through structured questionnaires. In which it helps encourage the young professionals to save and invest for retirement.